(untitled) (Modern Problems of Metallurgy, 2025)
The aim of the study is to provide an analytical synthesis of the theoretical foundations and practical approaches to improving energy consumption efficiency in the metallurgical industry, taking into account modern challenges of climate policy, rising energy prices, the need for decarbonization, and the economic feasibility of production process modernization. The methods. The research is based on an interdisciplinary analysis of scientific publications, international reports, statistical data, and techno-economic characteristics of steel production. Structural-comparative methods of analyzing energy consumption across different technological routes were applied, along with a systematic approach to assessing innovation potential and international benchmarking practices. Findings. The study identifies the main factors contributing to energy intensity in metallurgy and substantiates the technological reserves for improving efficiency, including the transition to electric arc furnace (EAF) steelmaking, the use of secondary raw materials, waste heat recovery, implementation of cogeneration, digitalization, and hydrogen-based metallurgy. Examples of successful modernization and national support programs from leading countries are also presented. The originality. The paper systematizes current energy efficiency indicators and production routes in steelmaking, characterizes the impact of various technological strategies on integrated energy intensity, and proposes criteria for assessing energy-saving potential at both macro and micro levels. Practical implementation. The results can be used to substantiate enterprise energy strategies, shape industrial decarbonization policies, prepare investment projects, and support the development of national and international programs to improve energy efficiency in the metallurgical sector.